Responsabilidade civil dos pais pelos danos causados pelos filhos menores - Oliveira, Ana Paula Cazarini Ribas de (2009)
This work for the Master´s degree has the aim of analyzing the topic of the parents´ responsibility for the damage caused by their children under majority. It is based on the Civil Code from 2002 that introduced two important changes: the straight responsibility of parents and in case they are not able of doing it or do not have enough possessions for satisfying this duty, the law hold responsible the incapable for the compliance with the obligation for the reparation of the victim. Such changes concerning the constitutional principles of the human being´s dignity, solidarity, equality, liberty and psychophysics integrity, the principle of the whole reparation for the damage suffered by the victim and the principle of the whole protection of the rights for the minor, according to the Child and the Teenage Statute combine with the aim of the general civil responsibility, allow the law to give the rules, that the matter is based on, a different comprehension concerning its content and covering. It is said that parents are responsible by the damage caused by their minor children because they were given cause, therefore they must afford the duty that might appear, independently of their marital status whether they are married (the fact or the right), separated, divorced or even if they were removed from the family power or whether it had been suspended. In any case, there will be solidarity between parents for the compliance with the obligation for the reparation. In this context, hypotheses that move away the parents´ responsibility are reduced. The chances of the victim to obtain the reparation for the damage suffered increase at the same time that there is the guarantee for more protection to the minor who might have his own property reached in case parents neither answer to the obligation of the reparation nor are responsible for it